Basic Assessment of Military Academy Cadets Selected on the Basis of Merit - Nugraha, Agung Yudha; Muslim, Muh Azis; Azhari, Yulian (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
Based on reports on the implementation of recruitment activities for Taruna and Taruni Akmil candidates in 2019 and 2020, several problems were found during the recruitment and selection process for Taruna Akmil. These problems certainly must be resolved by the Indonesian Army, with the aim of getting the best and quality Military Academy cadets. Departing from these problems, the researcher conducted an evaluation of the policy of the Army Chief of Staff Decree No. Kep/1023/XII/2016 concerning Technical Instructions on Admission of Military Academy Cadets and Cadets based on a merit system. This research was conducted using the literature review method. Several criteria are used to identify the application of the merit system during the recruitment and selection process for Akmil Cadets. These criteria are equal opportunity, open competition and fairness, and passing grade. The results found were that the recruitment and selection policies for Cadets of the Military Academy had supported the implementation of the merit system. However, problems occurred when the policy was implemented, which ultimately resulted in these criteria not being met during the recruitment and selection process for Academy Academy Cadet.